Hydraulic behavior, benefits and limitations of applying a SDGA to a flexible pavement structure - Reyes Lizcano, Freddy (2025)
The principal design criteria for flexible pavement structures have been based on the density and stability. In last years it has been detected that the behavior of these structures as drainage systems are not convenient, allowing important water infiltrations which affects its durability. Installation of an Open-Graded Drainage System (OGDS) in flexible pavement structures is thus convenient in order to reduce the harmful effects that can produce the infiltrated water. The present study is based on an experimental analysis in order to evaluate the hydraulic behavior, the benefits and limitations of the application of an OGDS in flexible pavement structures for extended operation periods in Bogota.To achieve this objective two experimental models were constructed, one representing a conventional flexible pavement structure and another representing a flexible pavement with a OGDS. The preliminary tests consisted of pouring water with methylene blue on each one of the constructed structures, allowing the visualization of its path across the layers. With this experiment it was concluded: ) asphalt surface presented a secondary permeability and the water infiltration is developed in few minutes; (li) on conventional flexible pavement structure model the water infiltrated was caught in the interface between the pavement surface and the granular base; (ili) on the model which includes an OGDS, the infiltrated water was evacuated immediately without accumulation zones. Due to the presence of solids in runoff water, it was conceived an experimental method in order to estimate the operation periods of this drainage system, based on the study of the runoff water characteristics for Bogota and the clogging of this system. With this study, the useful life of an OGDS was assessed as 5.43 years without taking into account the maintenance nor real hydrological behavior dry weather/storm weather periods. The results show the inclusion of an OGDS in flexible pavement structures could be an interesting method for the drainage of infiltrated water.